Efficacy of Natural Inhibitors against PKC: An In silico approach to combat Cancer - Arif2, M. Lohani2 and F. Jamal3, M. Kalim A. Khan1, M. H. Baig1, J. M. (Recent Research in Science and Technology, 2011)
Protein Kinase C (PKC), a member of isozyme family plays an important role in cell growth regulation and differentiation and is being considered as a novel target of many anti-cancer drugs. In this study we have explored the affinity and interaction of some natural plant derived compounds against PKCÃŽÂ± to find out some important active site amino acid residues that play an important role in the binding of inhibitors with the active site.